Multi-wavelength Čerenkov radiations in a microring resonator in combination with two gratings - Jomtarak, Rangsan; Yupapin, Preecha P. (My University, 2015)
In this paper, the Čerenkov radiation of light pulse in a microring and gratings is simulated and investigated. The system design consists of a two-defect grating incorporating a microring, connected with a uniform grating. In simulation, the continuous wave (CW) light pulse with wavelength centered at 1.55 μm is input into the microring device via the two-defect grating. The resonant outputs from the two-defect grating propagate through the microring and uniform grating, where the time delays of those two input pulses with different wavelengths through the system are distinguished by the output uniform grating. From the obtained resonant output pulses, we find that the red-shifted and blue-shifted Čerenkov pulses are observed. In applications, such a proposed system can be used to form two different optical delay pulses, in which the change in Čerenkov radiation of them, i.e., time delay within a microring device system, can be useful for Čerenkov radiation imaging and sensing applications.